A Beginner Book For Arabic Basic User: Analysys Al-Lughah Al-Arabiyah Book Chapter One Based On CEFR Standart - Tamam, Muhammad Ibnu; Syafni, Hafidhah; Rosyidi, Abdul Wahab; Fitra, Muh. Naufal (STIQ Amuntai, 2024)
The Arabic textbook MI Grade 1 KSKK is a book published by the Ministry of Religious Affairs in the context of implementing KMA Number 183 of 2019 concerning the PAI Curriculum and Arabic Language in Madrasas. This article presents the results of the analysis of MI Class 1 KSKK Arabic textbooks using CEFR standards. CEFR stands for Common European Framework of Reference established by the Council of Europe in 2001 as a response to the importance of learning foreign languages in order to use them in everyday transactions, be it social, interaction and information transfer. The purpose of this article is to find out the description of the MI Class I Arabic textbook, then at what level is this book in the CEFR standard and how are the CEFR principles contained in it. In its writing, this article uses a literature research method (literature review) with a content analysis approach, where researchers analyze all the material in this MI Class 1 Arabic textbook. The results showed that the Arabic textbooks of MI grade 1 KSKK were categorized in levels A1 and A2 based on CEFR standards. In addition, this book has also fulfilled CEFR principle 6, including language activities, language processes, text, domain, language learning strategies, and language tasks.